The Californios a history, 1769-1890 - Janin, Hunt 1940-; Carlson, Ursula 1943- (McFarland & Company, Inc., 2017)
"Before the Gold Rush of 1848-1858, Alta (Upper) California was an isolated cattle frontier...and home to a colorful group of Spanish speaking, non-indigenous people known as Californios. Many traces of their culture remain in California today. Drawing on firsthand contemporary accounts, the author chronicles the rise and fall of Californio men and women"...